2019
DOI: 10.2478/macvetrev-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Morphometry and Histogenesis of the Prenatal Dromedary (Camelus Dromedarius) Spleen

Abstract: Prenatal gross morphologic, morphometric and histologic developmental features of the dromedary spleen were studied. The dromedary gestation period (13 months) was categorized into four (1-4) phases and ten developing spleens per growth phase were sampled. Splenic topographical anatomy was noted before being eviscerated from each foetus. Morphologic and morphometric features of the eviscerated spleens were immediately documented and 2 – 4 mm thick samples were collected for histological analysis. The developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…At high magnification, the splenic cords are composed of reticular fibers, reticular cells and macrophages. Again, under the microscope it was found that the venous sinuses can occupy the entire surface of the red pulp including, they are lined with epithelial tissue and rest on a basement membrane, the periciliary arteries and arteriolar capillaries are also located in red pulp, data similar to research by [6] and [7] and [8].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…At high magnification, the splenic cords are composed of reticular fibers, reticular cells and macrophages. Again, under the microscope it was found that the venous sinuses can occupy the entire surface of the red pulp including, they are lined with epithelial tissue and rest on a basement membrane, the periciliary arteries and arteriolar capillaries are also located in red pulp, data similar to research by [6] and [7] and [8].…”
Section: Discussionsupporting
confidence: 79%
“…Its parietal surface is smooth, on the visceral surface there are elongated spleen doors, in the hilum area the spleen is relatively loosely connected with a large omentum. According to [8], predicts that the spleen is always adjacent to the left abdominal wall, its position largely depends on the fullness of the stomach. However, the spleen can accumulate up to 16% of all a dog's blood, affecting the displacement of the ventral end to the right half of the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…The results of morphometric study and mass of this organ on other mammals were conducted by Vashishtha et al (2018). Finding significant variations according to age, also, discussed a progressive increase of mass and revealed that sex has no influence on its development, results found by Jaji et al (2019). Measurement of fetal spleens, minimum value of length was 3.61 cm found in first group while maximum value was 4.35 cm found in fourth group.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the anatomical site of the spleen, the red fox's spleen is placed over the greater curvature of the stomach that is similar to the dog's spleen (Dyce et al 2010). Moreover, the spleen of the red fox contacts with the cranial pole of the left kidney while it is expanded to the caudal pole in camels (Jaji et al 2019). The red fox spleen is located in the left cranial quadrant of the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen is considered the largest reticuloendothelial hematopoietic tissue in animals. It is an elongated and relatively flat organ located in the cranial left abdominal region and attached to the stomach via small blood vessels (Maronezi et al 2015;Jaji et al 2019).…”
Section: Introductionmentioning
confidence: 99%